The correlation between serum zinc and vitamin D/25(OH)D in women with recurrent aphthous stomatitis - Hendri Susanto; Puput Kendarwati; Sri Budiarti; Supriatno Supriatno (Majalah Kedokteran Gigi Indonesia, 2019)
Recurrent aphthous stomatitis (RAS) is an oral mucosal disease which was more prevalent in women than men. Study has shown that zinc deficiency associated with the occurance of RAS. Other study also have shown that vitamin D deficiency contributed in RAS. However, there is no study yet that reveal the association between serum zinc and vitamin D/25 (OH)D in women with RAS. To investigate the association between serum zinc and vitamin D/25(OH)D in women with RAS. Thirty two women patients with RAS who meet the inclusion criteria participated in this study. The inclusions criteria was non pregnant women who have been diagnosed RAS and did not have other oral diseases. The exclusions criteria were those who have systemic diseases, taking medications including multivitamin, and have bad habits (i.e. smoking). Data concerning characteristic of subjects, severity of RAS, serum vitamin D/25(OH)D, and zinc were collected and presented descriptively. The correlation between serum zinc and Vitamin D/25(OH)D was analyzed using Pearson correlation test with 95% confidence interval. This study has been approved by Medical and Health Ethics Committe, Faculty of Medicine, Universitas Gadjah Mada, Yogyakarta. All subjects of this study have low mean value of serum vitamin D/25(OH)D (11.08 ± 3.11 ng/mL) and categorized with vitamin D deficiency. The subjects also have low mean value of serum zinc (54.78 ± 9.19 μg/dL) and seventy percent subjects have mean value of serum zinc below normal. The result of Pearson correlation test showed that there was a significant positive correlation between mean serum zinc and Vitamin D/25(OH)D (r= 0.351, p<0.05) in women with RAS. Serum zinc associated with vitamin D/25(OH)D and play role in pathogenesis of RAS.